2006
DOI: 10.1111/j.1464-410x.2006.06390.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and bother of nocturia, and causes of sleep interruption in a Danish population of men and women aged 60–80 years

Abstract: RESULTSIn all, 92% (3664) subjects returned the questionnaire; 71% completed the questionnaire satisfactorily and were included in the study. The prevalence of nocturia increased with age. The overall prevalence of nocturia was 77% and there was no difference between men and women ( P = 0.11), but men had slightly more severe nocturia than women. The bother caused by nocturia in men and women increased with the severity of nocturia, and women were slightly more bothered than men when the degree of nocturia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 30 publications
2
89
0
4
Order By: Relevance
“…34 In a study by Bing et al, the prevalence of nocturia was found to be similar in men and women. 21 However, men had more severe nocturia than women, whereas women were more bothered than men by nocturia. It is a well-known fact that subjective quality of sleep is generally poorer in women than in men.…”
Section: Sexmentioning
confidence: 97%
See 3 more Smart Citations
“…34 In a study by Bing et al, the prevalence of nocturia was found to be similar in men and women. 21 However, men had more severe nocturia than women, whereas women were more bothered than men by nocturia. It is a well-known fact that subjective quality of sleep is generally poorer in women than in men.…”
Section: Sexmentioning
confidence: 97%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]78,79 Many cross-sectional studies after the millennium have shown an independent association of older age with nocturia after multivariate analysis.…”
Section: Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have presented the optimal economic model for the evaluation of OSAHS. In a Danish Health Technology Assessment, the use of ambulatory portable diagnostic procedures using partial polygraphy followed by auto-adjusted CPAP was superior to the use of in-hospital, supervised PSG (which is time consuming and costly) and oximetry (which has low sensitivity and diagnostic accuracy) among patients without major comorbidity in the primary care sector [74]. Similar results have been obtained by others, who found oximetry to present low diagnostic accuracy, but also pointed out the use of split-night PSG studies as an alternative diagnostic and therapeutic approach [75].…”
Section: Screening and Management Of Sleep Apnoeamentioning
confidence: 99%